An adaptive context-aware mobile learning framework based on the usability perspective. (16th December 2010) - Yau, Jane Yin-Kim; Joy, Mike
Three different types of context-aware mobile learning applications were revealed in our literature review – location-dependent, location-independent and situated learning. Our theoretical framework – mobile context-aware adaptive learning schedule was constructed. This uses a proactive approach – the learner's schedule (i.e. an electronic organiser) to retrieve the location and time available contexts. Other contexts are also considered – learning styles, knowledge level, concentration level and frequency of interruption. Thereafter, appropriate learning materials are recommended to students based on this information. We utilised a diary: diary-questionnaire research methodology for our usability feasibility in which 32 university students had participated in.